A Descriptive Study of Preoperative Anxiety Levels and Vital Sign Stability Among Patients at Puruk Cahu Regional General Hospital - Agus Saputra; Muhammad Arief Wicaksono; Rian Tasalim (Universitas Ibn Khaldun Bogor, 2026)
The preoperative period is a crucial phase in surgical care, during which patients frequently experience psychological distress, particularly anxiety. Anxiety may arise from uncertainty about the surgical procedure, anesthesia, potential complications, and postoperative outcomes. Previous studies indicate that 40-80% of surgical patients experience preoperative anxiety at varying levels. This emotional response can activate the sympathetic nervous system, leading to physiological changes such as increased blood pressure, heart rate, and respiratory rate. If not properly identified and managed, these alterations may affect perioperative stability and recovery. This study aimed to describe preoperative anxiety levels and the stability of vital signs among patients at Puruk Cahu Regional General Hospital. A quantitative descriptive study with a cross-sectional design was conducted involving 30 adult patients scheduled for elective surgery, selected through purposive sampling. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). Vital signs including blood pressure, pulse rate, respiratory rate, and body temperature were assessed using standard hospital equipment. Data were analyzed using descriptive statistics and presented as frequencies and percentages. The results showed that 33.3% of patients had no/normal anxiety, 30.0% had moderate anxiety, and 33.3% experienced severe anxiety, while 3.3% had mild anxiety. Abnormal blood pressure was found in 80.0% of patients, whereas most had normal pulse rate (73.3%), respiratory rate (93.3%), and body temperature (93.3%). These findings highlight the importance of comprehensive preoperative psychological and physiological assessment.